Synthesis and Complexation of a Free Germanide Bearing a Tridentate N-Heterocyclic Substituent - Witteman, Léon (Organometallics, 2019)
[Image: see text] The tris-N-heterocycle germanide (tmim)Ge(–) (1) (tmimH(3) = tris(3-methylindol-2-yl)methane) was synthesized by nucleophilic substitution for the tmim(3–) trianion on GeCl(2)·dioxane. In combination with the previously reported (tmim)Si(–) and (tmim)P analogues, it provides a convenient model for investigating the influence of the central atom on the properties of isoelectronic ligands. Complexation of the germanide (tmim)Ge(–) to CuCl resulted in the dimeric chloro cuprate [(tmim)GeCu(μ-Cl)](2)(2–), which is prone to dissociation in MeCN to form the neutral, solvated germylcopper (tmim)GeCu(NCMe)(3). The reaction of 1 with Fe(2)(CO)(9) afforded the germyl iron tetracarbonyl [(tmim)GeFe(CO)(4)](−). Analysis of the ν̃(CO) infrared absorption bands in this complex indicates that the combined electron donating and accepting properties of 1 are found in between those of (tmim)P and (tmim)Si(–). In contrast to (tmim)Si(–), (tmim)Ge(–) is reluctant to coordinate to FeCl(2), likely because of its softer Lewis base character. Key structural features of the ligands and complexes reflect changes in their electronic properties. In particular, the N–Ge–N angles increase upon coordination to a metal fragment, suggesting increasing hybridization of the Ge s- and p-orbitals. These findings will be useful in further understanding low-valent heavier group 14 complexes in organometallic chemistry.